Vers une théorisation de la distinction entre l'oral et l'écrit - Chovancová, Katarína (Verbum – Analecta Neolatina, 2006)
Different kinds of computer mediated communication combine contradictory properties. On one hand, there are typical features of spoken language, on the other, there are parameters traditionally associated to written productions. We propose three levels of distinction between spoken and written language: material form, conditions of production, and structure of the final product. Spoken and written language, conceived as two different strategies of expression, cannot be limited to the material realization of language. Other parameters to be taken into consideration are the co-presence of the interacting partners and, consequently, the possibility of direct feedback. Some discourse have mixed characteristics, situating themselves between the ideal categories of spoken and written language.